School Factors Strongly Impact Transgender and Non-Binary Youths' Well-Being - Janie Kelley; Annie Pullen Sansfaçon; Morgane A. Gelly; Lyne Chiniara; Nicholas Chadi (MDPI AG, 2022)
Background: School plays an important role in transgender and non-binary (TNB) youths' life and well-being. The aim of this study was to gain a better understanding of how the lived experiences, gender affirmation and challenges encountered by TNB youths in the school setting affect their well-being. Method: Our study was a qualitative secondary data analysis, based on the interviews of 12 Canadian TNB youths aged 15-17 years old. Results: We found that TNB students' well-being was closely related to the acknowledgment of gender identity at school. Several factors, including school socio-cultural environment, teachers' and peers' attitudes and behaviours, school physical environments and the respect of confidentiality of gender identity were all found to impact TNB students' well-being. To face adversity related to some of these factors, TNB youths used several contextually driven strategies such as compromising, educating, and sensitizing others about gender diversity and avoiding certain people or situations. Conclusion: Our results highlight the important influence of school climate and culture, as well as teachers', school personnel's and peers' behaviours and attitudes on TNB youths' well-being. Our findings can guide future interventions to help schools become more inclusive and supportive of gender diversity.